Análise da expressão dos genes relacionados à parede celular e a membrana plasmática de Saccharomyces cerevisiae em resposta a alta pressão hidrostática - Souza, Diego Trindade de (2012)
The yeast Saccharomyces cerevisiaehas received much attention for its applications in the biotechnology industry. However, during these processes, yeasts are exposed to many different types of stress. Knowing the mechanisms S. cerevisiaeuses to respond to these stresses is essential for obtaining higher yields in the industrial sector. High hydrostatic pressure (HHP) is a stress that exerts a broad effect on S. cerevisiae, interfering with cell membranes, cellular architecture, and various biochemical processes. In this study, we used the microarray technique to investigate the influence of HHP on genes related to the cell wall and plasma membrane. For this, cells from BT0605 strain were subjected to hydrostatic pressure of 50 MPa for 30 min, and then incubated at ambient pressure for 5, 10 and 15 min.The microarray results clearly demonstrated that of the genes involved in biogenesis of the cell wall, those which are related to protection were readily activated by high pressure, whilst the genes involved in cell wall structure required 5 minutes on the ambient pressure to be induced.